Baseline imaging characteristics and early structural changes in macula on rhegmatogenous retinal detachment - Alberto Quarta; Matteo Gironi; Maria Ludovica Ruggeri; Agbeanda Aharrh-Gnama; Annamaria Porreca; Rossella D’Aloisio; Lisa Toto; Marta Di Nicola; Rodolfo Mastropasqua (Scientific Reports, 2024)
Abstract Animal models have demonstrated that structural changes affect the macula during peripheral rhegmatogenous retinal detachment. This study aimed to assess photoreceptors, retinal and choriocapillaris perfusion in non-macula involving rhegmatogenous retinal detachment by analyzing en-face images from structural OCTA segmented at the ellipsoid zone (EZ) level, calculating (1) “normalized” reflectivity as a surrogate biomarker of photoreceptor damage (2) perfusion density (PD), vessel length density (VLD) and vessel diameter index (VDI) of superficial capillary plexus (SCP) and deep capillary plexus (DCP) (3) perfusion density of choriocapillaris (PDCC). Twenty-one eyes affected by macula-on rhegmatogenous retinal detachment (RRD) were enrolled at the University “G. d’Annunzio”, Chieti-Pescara. The fellow unaffected eye was used as control. The mean age at the onset of RRD was 60.09 ± 10.22 (range 34–83). Compared with fellow eyes, we found lower EZ “normalized” reflectivity in macula-on (0.42 ± 0.15 in fellow eyes and 0.31 ± 0.09 in macula on p = 0.004). The affected eye was also characterized by impaired perfusion in SCP (17.26 ± 3.34% in macula on and 20.56 ± 3.62% in the fellow eye p = 0.004) and CC (50.21 ± 6.20% in macula on the eye and 57.43 ± 6.20% in the fellow eye p = 0.004). Macula-on rhegmatogenous retinal detachment has subclinical changes in photoreceptors, SCP, and CC. Future longitudinal studies should evaluate if early changes could impact post-operative macular function.